The Effect of Circadian Blood Pressure in The Development of Lacunar Infarcts, Together with Other Possible Factors - KESKİN, Gökhan and ÇAKMAK, Abdulkadir (International Journal of Computational and Experimental Science and Engineering, 2021)
This study was carried out in Amasya University S.S.R.E. Hospital Department of Neurology and Cardiology between 2021 and 2022. Total number of 58 patients (29 lacunar infarct patients and 29 control subjects, 42 females and 16 males) over the age of 45 (mean age 57.1+-6.8) were recruited to the study. All patients underwent 24-hour blood pressure monitoring. The patients with a history of stroke, malignancy, renal or endocrinal disease were excluded from the study. According to the systolic blood pressure measurements, twenty-seven patients were ‘non-Dipper’ and thirty-one patients were ‘Dipper’. Diastolic blood pressure measurements revealed that twenty-one patients were ‘non-Dipper’ and thirty-seven patients were ‘Dipper’.Mean daytime and night-time systolic blood pressure values were higher in patients with lacunar infarction (p:0.02). There was no difference in the diastolic BP and variability (p > 0,05). The clinical importance of the alteration in the reduction of blood pressure is still controversial. Understanding the alterations in blood pressure rhythmicity will be helpful to prevent and treat the lacunar infarctions.